Pola Komunikasi PT. Doyan Group Dalam Meningkatkan Produktivitas Kerja - Zefanya, Aulia Neva; Leonindhira D, Agnes Gina; Rhuomena W, Arian; Amalia, Diana (Jurnal Ilmiah Wahana Pendidikan, 2024)
The communication process is the conveying of one's thoughts and feelings (the communicator) to another person (the communicant) and in a reciprocal manner. Where communication is a part of human activity. Communication patterns in the way an individual or group works in a group based on communication theory. The method used is a descriptive qualitative method, and data collection techniques are in-depth interviews and direct observation with a case study approach that focuses on Communication Patterns at PT. Doyan Group. The subject of this research is the Leader of PT. Doyan Group. The results of this research are that PT. Doyan Group implements an all-way communication pattern and always conducts regular evaluations